EXPLICATION THE CATEGORY OF THE NEGATIVE EVALUATION BY MEANS OF THE VERBS OF REPRESENTATION IN DISCOURSE - Островська, Олександра; Поплавська, Людмила (Current Issues of Foreign Philology, 2021)
This article is devoted to the analysis of the peculiarities of the realization the category of evaluation in discourse by means of the verbs of representation with the seme of the negative evaluation. The category of evaluation as the linguo-stylistic conception is defined as appraisal meaning within semantic structure of the word which realizes the attitude of the language collective to the words correlation with the word conception or object (good/approve). The category of evaluation is closely connected with the denotative and connotative meanings. The word in the plan of content can be distinguished as positive and negative and in plan of expression as implicit or explicit. In the context the word can attain an evaluative component of bad quality and this component can be realized implicitly or explicitly depending on the author’s outlook. The category of evaluation is characterized as the structure of the lexico-semantic field. The article is devoted to the peculiarities of the realization of the category of evaluation in the discourse by means of the verbs of representation with the seme of the negative evaluation. These verbs are divided into three groups: (a) the verbs which possess a distinctive seme “evaluation”. The verb “to hate” which is the particularly productive is regarded as a nucleus of the lexico-semantic field of the category of evaluation with the negative meaning. The verbs to dislike, to disgust, to blame, to annoy to irritate are included to the periphery of this field. (b) the verbs which express an evaluation contextually. Among the verbs of evaluation besides those that belong to the lexico-semantic field to hate it is possible to distinguish some verbs which within the certain context can express the negative evaluation. These verbs are: to doubt, to hesitate, to fail, to kill, to trouble, to envy. (c) the verbs of substitution to do, to be The verb to do is often qualified not only as the auxiliary verb, but also as the representative. According to our research the verb to do in the negative form can realize it evaluation meaning, that is transfer from the positive to negative field and v.v. The verb to be is considered as a verb of representation and also as a link verb. The verbs of substitution can be considered as the auxiliary and representative. In both of these functions they explicate the category of evaluation.